Avaliação in vitro da atividade antibacteriana do azul de metileno em diferentes formulações utilizados na terapia fotodinâmica na endodontia - Londero, Aline de Moraes (2014)
The persistence of microorganisms in the root canal system after chemical-mechanical preparation plays an important role in the success rate of endodontic treatment. Photodynamic Therapy in endodontics appeared to be a supplement to the disinfection of root canals aiming resolve this persistence. When questioning what the actual antibacterial effect of this treatment in clinical endodontics, we face numerous formulations and concentrations of the photosensitizer used, as well as numerous methodologies to test its antimicrobial activity, offering confusing and inconclusive results. The aim of this study was to evaluate the in vitro antibacterial activity against two strains of Enterococcus faecalis ATCCs 29212 and 51299, of the methylene blue photosensitizer (PS) in different formulations and concentrations cited in the literature. The method used to evaluate the antibacterial activity of the photosensitizer was the microdilution to determine the minimum inhibitory concentration. The 18 test substances, in the literature, were left in contact for five minutes in each well and then followed by the application of the laser (660 nm, Kondortech®, São Carlos, SP, Brazil) for three minutes. The tests were performed according to the Clinical and Laboratory Standards Institute (CLSI 2013). After the incubation period at 35 ± 2 ° C 18-24hs, read visually observing the bacterial growth and is considered where the inhibitory substances were wells without turbidity and / or deposition of sediments at the bottom was carried out. Dissolved in a mixture of 2% chlorhexidine and H₂O₂ (substance 15), and a mixture of glycerol, ethanol, water, hydrogen peroxide and Triton X100 detergent (substance 10) PS inhibited the growth of Enterococcus faecalis resistant microorganism 29212. For the addition of these the mixture PS glycerol, ethanol, and water (substance 13) also showed an inhibitory power. No concentration of methylene blue dissolved in water (300 to 7.5 μmol / L) had able to inhibit the growth of the strains analyzed. Given the literature reviewed and the results of the study to predict the efficacy of PDT against microorganism problem in endodontics, a standardization of the optimal formulation of PS, its contact time and also of important laser parameters is still necessary, as full power , creep and irradiation time.